Perspektif Pertukaran Sosial dalam Perilaku Politik Masyarakat pada Pilkada Kota Malang 2013 - Haliim, Wimmy (Jurnal Politik Indonesia: Indonesian Political Science Review, 2017)
This research tries to generate the surface related to the emergence of an interesting phenomenon on the people political behavior in Malang. It turns out that the results of the study, the researcher found four factors influenced the political behavior. They are exchange values of the family and psychological effect on political behavior, close relation towards the community and exchange of trust between candidates and voters, exchange of economy and its influence on political behavior and exchange of expectations changes from candidate to the people. This research shows that there are some factors which influence voters to vote the candidate. First, they who vote based on the family relation, on their figures. Then, apart from the two forms of behavior that have been mentioned earlier, because of the proximity of the candidate with the community and other rational reasons, such as money politics. These phenomena happened in every political behavior of community. As stated in social exchange theory, that is mentioned social interactions in various structures of society will occur if there is a mutual exchange, in the form of material or non-material.